Union Seniority Rules as a Determinant of Intra-Firm Job-Changes - Chaykowski, Richard; Slotsve, G.A. (Relations industrielles / Industrial Relations, 1986)
Micro-data from a Canadian industrial union establishment are explored in order to ascertain the extent to which seniority rules determine job-change decisions.